A Study of Caring Behavior among Nursing Students - Nurwijayanti, Andriyani Mustika; Septian, Cindi; Aeni, Qurrotul; Anggraeni, Rina (Global Health Science Group, 2025)
Caring behavior can be seen in nurses in providing nursing care, namely listening attentively, the presence of nurses when needed, building relationships of trust, responsibility, compassion, care, providing information, providing touch, providing encouragement and showing respect for patients. The application of caring behavior is not only applied by nurses who are already working, but must also be applied by nursing students who will later become nurses. The purpose of this study was to identify the level of knowledge of STIKES Kendal nursing students about caring behavior. This research method uses descriptive research design. The sample in the study amounted to 154 with students in semester 3, 5 and 7. Sampling using total sampling. The results showed that the knowledge of STIKES Kendal students in knowing caring behavior was mostly less 114 (74,03%). Nursing students need to maintain knowledge about caring behavior that is very good to form the soul and characteristics of being a professional nurse.